Pelatihan dan Pendampingan Implementasi Lesson Study Untuk Peningkatan Profesionalisme Guru dan Keterampilan Berpikir Kritis siswa Pada Pelajaran Fisika di SMAN 1 Sakra - Sapiruddin Sapiruddin; Baiq Aryani Novianti; Khaerus Syahidi; Tsamarul Hizbi (Universitas Muhammadiyah Mataram, 2024)
The purpose of this PKM is that teachers understand the concept of lesson study, are able to carry out lesson study and can implement lesson study in the process of learning activities, especially in physics subjects so as to improve students' critical thinking skills. This service activity starts from the preparation stage and the implementation stage. The partners in this PKM programme are physics teachers of SMAN 1 Sakra, the number of participants involved in this PKM activity is 9 people consisting of 2 Physics Education lecturers, 5 physics teachers of SMAN 1 Sakra and 2 students to help with documentation activities. The method used in this activity is Lesson study training and lesson study implementation assistance in the process of learning activities. The results achieved from this activity are (1) Increased teacher understanding of Lesson Study and (2) Increased teacher enthusiasm in improving lesson study-based learning. (3) Increased interest and confidence of teachers to become professional teachers (4) Increased critical thinking skills of students in physics subjects.